New National Air-Kerma-Strength Standards for (125)I and (103)Pd Brachytherapy Seeds - Seltzer, Stephen M. (J Res Natl Inst Stand Technol, 2003)
The new U.S. measurement standard for the air-kerma strength from low-energy photon-emitting brachytherapy seed sources is formally described in detail. This instrument-based standard was implemented on 1 January 1999, with its salient features and the implications of differences with the previous standard given only through a series of informal communications. The Wide-Angle Free-Air Chamber (WAFAC) is specially designed to realize air kerma from a single-seed source emitting photons with energies up to about 40 keV, and is now used to measure the wide variety of seeds used in prostate-cancer therapy that has appeared in the last few years. For the two (125)I seed models that have been subject to both the old and new standards, the new standard reduces the air-kerma strength by 10.3 %. This change is mainly due to the removal of the influence on the measurement of the Ti K x rays produced in the source encapsulation, a component with no clinical significance.